Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).

Access to NHC-Boryl mono- and bis-selenide and utility as mild selenium transfer reagent including to the C-F bond - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (Chemistry- a european journal, 2024)
Reactions of 5-SIDipp & sdot; BH3 (5-SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene) (1) with diphenyldiselenide provide access to 5-SIDipp-boryl mono- (5-SIDipp & sdot; BH2SePh) (2) and bis-selenide (5-SIDipp & sdot; BH(SePh)2) (3). The facile cleavage of the B-Se bond makes 2 a neutral source of selenium nucleophiles in substitutions reactions with benzyl bromides, and provide access to the corresponding selenoethers. The direct transformations of one of the C(sp2)-F bonds of C5F5N and C6F5CF3 to C-Se bonds have also been achieved by the use of 2 without employing transition-metal catalysts. While it was previously established that C6F6 could undergo complete defluoroselenation under harsh conditions, we successfully achieved partial defluorination of C6F6 by employing 2 as a mild selenide transfer reagent. During the formation of C-Se bonds through the cleavage of C-F bonds, the potential by-product NHC & sdot; BH2F undergoes ring expansion of the NHC, leading to the formation of the six-membered diaazafluoroborinane (7). Access to NHC & sdot; boryl mono- and bis-selenides from NHC & sdot; BH3 has been achieved. The boryl mono selenide has been demonstrated to function as a selenium transfer reagent, enabling the synthesis of selenoethers from benzyl bromide. Additionally, it can also facilitate the conversion of the challenging aromatic C-F bond to a C-Se bond, resulting in concomitant ring expansion of NHC & sdot; haloborane.image
Keywords: boron; C-F Bond Activation; N-Heterocyclic carbene; Ring expansion; Selenium